Selection of Methods of Proving the Inability of Debtors to Pay Debts and the Application of Prejudice Against Misuse of Insolvency Institutions in Insolvency Law in Indonesia - Yonatan YONATAN; Bambang SUGIRI; Sukarmi SUKARMI; Faizin SULISTIO (International Journal of Environmental, Sustainability, and Social Science, 2023)
In determining the inability of the Debtor to pay his debts to the Creditor known 2 (two) methods, namely: First, the Insolvency Test; Second, the use of prejudice of not being able to pay debts (Presumption of Inability to Pay). The Indonesian state uses the prejudice method of not being able to pay debts (Presumption of Inability to Pay), so the terms of bankruptcy become very simple. This article discusses the use of methods to determine the inability of the Debtor to repay debts associated with the prejudice to abuse (presumption of abuse) of the insolvency institution. The research method used in this article is normative juridical research with a statutory approach, a comparison approach, and a conceptual approach. There are several research results, namely; First, the politics of Indonesian insolvency law is time to change from prioritizing debt repayment to prioritizing Business Reorganization as found in the United States.; Second, it is time for the Indonesian state to abandon the prejudiced method of not being able to pay debts (Presumption of Inability to Pay) to use the Insolvency Test method to determine the incompetence of debtors in repaying debts.